Country Insurance : Reducing Systemic Vulnerabilities in Latin America and the Caribbean - World Bank (Washington, DC, 2012)
This study begins from the premise that output and consumption are more volatile and prone to sharp contractions in developing than in high-income economies. This suggests that developing countries are somehow "underinsured" and may thus need to invest more in "country insurance" policies. To shed some light on this issue, the author begin by providing in the first chapter evidence of the excessive volatility faced by developing countries in general (and Latin American and Caribbean, LAC, countries in particular) and then discuss some of the welfare costs associated with such volatility. In second chapter, the author focus on the main trade-offs and on the strategic choices confronted by developing countries if they decide to increase their resilience to external shocks. Finally, in the third chapter, the author look at different policy options, focusing on how the international financial institutions (IFIs) in general and the World Bank in particular can help developing countries' reduce their vulnerability to external shocks. While excessive volatility in developing countries affects both government and the private sectors, this study limits its focus to the government sector. The private sector challenges will be addressed in future research.